2017
DOI: 10.18632/oncotarget.19857
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10gene rs1800896 polymorphism is associated with the risk of prostate cancer

Abstract: Numerous studies have uncovered the association of Interleukin-10 (IL-10) gene rs1800896 polymorphism with the risk of prostate cancer (PCa); however, their conclusions were inconsistent. Therefore, we conducted this meta-analysis to evaluate the role of IL-10 rs1800896 polymorphism in the risk of PCa. 16 eligible studies in 15 articles involving 6,301 cases and 6,510 controls were identified by researching PubMed, Google, CNKI, and EMBASE up to April 1, 2017. Our results revealed that IL-10 rs1800896 polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…A previous study suggested that the secretion of IL-10 is determined largely (74%) by heritable factors 23 . Several studies have found an association between the IL-10 -1082 G/A polymorphism and oral cancer,head and neck cancer 24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study suggested that the secretion of IL-10 is determined largely (74%) by heritable factors 23 . Several studies have found an association between the IL-10 -1082 G/A polymorphism and oral cancer,head and neck cancer 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that the secretion of IL-10 is determined largely (74%) by heritable factors 23 . Several studies have found an association between the IL-10 -1082 G/A polymorphism and oral cancer,head and neck cancer 24 , 25 . Because meta-analysis is a suitable method to evaluate small effects in genetic association studies, we designed this study to systematically evaluate the association of the IL-10 -1082 G/A polymorphism with HCC risk.…”
Section: Discussionmentioning
confidence: 99%
“…A study looking for the participation of variant alleles at both −819 and −592 polymorphisms was modestly associated with the advanced stages of prostate cancer [82,83]. Other meta-analysis reports that rs1800896 polymorphism is associated with a decreased risk of prostate cancer [84].…”
Section: Diseasementioning
confidence: 99%
“…SNPs in the transcriptional start area of IL-10 gene influence the production of IL-10 thus may increase or decrease the risk of cancers, [ 10 12 ] including leukemia, but the conclusions are inconsistent. For example, Ovsepyan, V. A. et al [ 13 ] found SNP in the IL-10 -1082A/G was associated with the risk of chronic lymphoid leukemia, while Lo, W. J. et al [ 14 ] found no association between IL-10 -1082A/G and leukemia.…”
Section: Introductionmentioning
confidence: 99%